The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.20452/pamw.4293
|View full text |Cite
|
Sign up to set email alerts
|

Nonadherence to the protocol regarding potassium replacement results in prolonged diabetic ketoacidosis management

Abstract: Introduction Diabetic ketoacidosis is a life-threatening condition that requires prompt management. Objectives We aimed to assess the impact of adherence to potassium replacement protocol according to the guidelines of Diabetes Poland on the duration of diabetic ketoacidosis (DKA) treatment. Patients and methods This retrospective analysis included 242 adults (median age, 27 years; range, 21-38 years). Nonadherence to potassium replacement protocol was assessed, along with the relationship between nonadherence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The extent of non-adherence to the treatment protocol for the management of DKA is also a reason for hypokalemic events 76. Abela et al56 reported that potassium was given to the patients at a later stage of DKA resolution, with the main reasons being lack of clear instructions or secondary to not following the DKA management protocol to analyze the blood for potassium concentration; importantly, the volume of potassium resuscitation was higher and aggressive when initiated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of non-adherence to the treatment protocol for the management of DKA is also a reason for hypokalemic events 76. Abela et al56 reported that potassium was given to the patients at a later stage of DKA resolution, with the main reasons being lack of clear instructions or secondary to not following the DKA management protocol to analyze the blood for potassium concentration; importantly, the volume of potassium resuscitation was higher and aggressive when initiated.…”
Section: Discussionmentioning
confidence: 99%
“…Although the well established guidelines strongly give recommendations regarding potassium monitoring and supplementation in DKA, none of these guidelines suggest using the pH-adjusted corrected potassium level to initiate potassium resuscitation or adjust the treatment plan 47. And on top of it, count to carry out the recommendations for potassium resuscitation remains very low, regardless of time, whether it is observed in the distant9,48,54,56,71 or near past 76. Even further, despite all the included studies in the current review that were either depicting important parameters of DKA or experimenting with its management to improve patient oriented outcomes, not a single study demonstrated the impact of potassium and acidosis on cardiovascular outcomes in DKA patients, which remains an area to explore further.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid hypokalaemia, we recommend measuring serum potassium 2 h after starting insulin administration and every 4 h thereafter until the resolution of DKA. Use of too low or too high doses of potassium compared with the recommended potassium replacement protocols in the management of DKA has been associated with longer hospital stays [148].…”
Section: Section 4 What Is the Recommended Treatment Of Dka And Hhs?mentioning
confidence: 99%
“…To avoid hypokalemia, we recommend measuring serum potassium 2 h after starting insulin administration and every 4 h thereafter until the resolution of DKA. Use of too low or too high doses of potassium compared with the recommended potassium replacement protocols in the management of DKA has been associated with longer hospital stays (148).…”
Section: Potassiummentioning
confidence: 99%